Iran's Nuclear Programme : Strategic Implications. - Krause, Joachim (Routledge global security studies., 2011)
This book examines the strategic implications of Iran's nuclear programme, providing an inventory of the negotiations and a discussion of possible solutions to this pressing international security issue. The Islamic Republic of Iran's nuclear programme has been the cause of one of the most extended international crises of the past decade. Multilateral institutions have been unable to resolve the issue, which has the potential to derail the global nuclear non-proliferation regime. Recent failures of diplomatic offers for an extended Iran-EU cooperation and projected US arms sales to Iran's neig.